Social cost of carbon: A revisit from a systems analysis perspective - Khabarov, Nikolay; Smirnov, Alexey; Obersteiner, Michael (Frontiers in Environmental Science, 2022)
Social cost of carbon (SCC) is estimated by integrated assessment models (IAM) and is widely used by government agencies to value climate policy impacts. While there is an ongoing debate about obtained numerical estimates and related uncertainties, little attention has been paid so far to the SCC calculation method itself. This work attempts to fill the gap by providing the theoretical background and economic interpretation of the SCC calculation approach implemented in the IAM DICE (Dynamic Integrated model of Climate and the Economy). Our analysis indicates that the present calculation method is unable to catch the linkages between two key IAM's components -- complex interconnected systems -- climate and economy, both influenced by emission abatement policies. Within the modeling framework of DICE, the presently estimated SCC valuates emissions, which are beyond policy control, against consumption of products, which cannot be produced by economy. This makes SCC irrelevant for application in climate-economic policies and, therefore, calls for a replacement by a more appropriate indicator. An apparent SCC alternative, which can be considered for policy formulation, is the direct output of the DICE model -- the socially optimal marginal abatement cost (SMAC), which corresponds to technological possibilities at optimal level of carbon emissions abatement. In policy making, because of the revealed SCC deficiency, great attention needs to be paid to the use of estimates obtained earlier.